The Meaning of Legong Dedari Performance in Banjar Abian Nangka Kaja, Kesiman Petilan, East Denpasar - Ni Nyoman Manik Suryani; Ruastiti Ni Made; Katie Basset (Mudra Jurnal Seni Budaya, 2023)
The Legong Dedari is one of the sacred dances performed by the Balinese Hindu community at Banjar Abian Nangka Kaja, Kesiman Petilan Village, East Denpasar. Despite the fact that this dance is frequently performed for ceremonial offerings, no one has studied the Legong Dedari dance. This article aims to discuss the form and meaning of the Legong Dedari dance. The data sources for this research were the Legong Dedari dance performance itself, the dancers, musicians, traditional leaders, village elders, and the local community, who were selected based on purposive sampling and snowball techniques. All the data that has been collected through observation, interviews, and literature studies was analyzed descriptively and qualitatively using structural-functional theory and aesthetic theory. The results showed that the Legong Dedari dance, which is a wali dance (sacred dance), is presented in the form of a loose dance. This can be seen in the manner of presentation, fashion make-up, performance structure, and musical accompaniment. The Legong Dedari dance, which is danced by three female dancers who use delicate princess make-up, is accompanied by Gamelan Gong Kebyar. The community in Banjar Abian Nangka performs this Legong Dedari dance during piodalan ceremonies in the local area, along with Ratu Ayu's sasuhunan on Tumpek Wayang, Tumpek Uduh, and when a prolonged disaster occurs. The local community has continued to preserve the Legong Dedari Dance because the dance contains religious meaning, aesthetic meaning, social meaning, & ecological meaning.